Development of vulnerability curves of buildings to windstorms using insurance data: An empirical study in South Korea - Yum, Sang-Guk; Kim, Ji-Myong; Wei, Hsi-Hsien (Journal of Building Engineering, 2021)
Windstorms have caused a range of damage on the built environment. Although several risk assessment models for estimating such damage have been widely developed, the results generated by these models often turn inaccurate due to the building information required for such models at a regional scale are usually incomplete, or of a poor quality. Alternatively, this study utilizes an insurance company's loss data pertaining to the high winds of Typhoon Maemi in South Korea in 2003 for calculating building damage in terms of damage ratios. Next, these damage ratios and storm-wind speeds are utilized for constructing vulnerability curves that can be used to predict levels of damage to designated building types subject to given wind speeds. Lastly, geographical information systems spatial data is combined with those vulnerability curves to arrive at four distinct wind-damage levels. It is hoped that the present research will serve as a reference for further studies of developing building vulnerability curves for storm winds. •Estimates wind-induced property damage/financial losses using vulnerability curves .•Utilizes a binomial method for analyzing a damage dataset .•Uses a novel combination of MSE and MLE to compute vulnerability curves .•Financial loss data associated with wind speeds takes the form of a ratio .